The use of the Nuovo Soggettario for semantic indexing of web resources: issues and proposals - Elisa Bianchi; Maria Clotilde Camboni; Elena Lazzarini (JLIS.it, 2013)
The essay deals with the creation of subject-headings for web resources related to Italian literature, art and linguistics with resort to the Nuovo soggettario system (NS). It describes the difficulties arisen and the results achieved in this regard during the development of a project aimed at creating web tools to facilitate the location of high quality web resources about Italian culture. One of these tools was a catalogue of web resources with subject headings, created using a modified version of the MICHAEL Data Model. The authors explain why they had to change the model to meet the needs set by the peculiar items of the catalogue, why the choose the NS for the subject-headings, their choices about the granularity of the description, their particular use of the “Intellectual/Bibliographic form” roles of the NS to match the features of their items that could be relevant for a user, and their consequent proposals of new terms for the NS Thesaurus and the questions that arose from these proposals.